Prevalence of mucoepidermoid carcinoma among intraoral minor salivary gland tumors: A systematic review and meta‐analysis. (4th July 2020) - Poletto, André Goulart; Mello, Fernanda Weber; Melo, Gilberto; Rivero, Elena Riet Correa
Abstract: This study aimed to synthetize and critically appraise available evidence regarding mucoepidermoid carcinoma (MEC) prevalence among intraoral minor salivary gland tumors (MiSGT). Five main electronic databases and three grey literature databases were searched. The risk of bias (RoB) was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data. Proportion meta‐analyses were performed. From 1321 studies identified, 82 were included in qualitative synthesis and 80 in meta‐analyses. Sixteen were classified as high, 33 as moderate, and 33 as low RoB. A total of 12 774 MiSGT were found, of which overall MEC prevalence was 16.5% (95% Confidence Interval [95% CI] = 14.8%‐18.4%). Most MiSGT were found in the palate (n = 7115), although MEC pooled prevalence in this anatomic location was only 13.6% (95% CI = 11.7%‐15.6%). The retromolar area presented the highest pooled prevalence (58.9%; 95% CI = 47.0%‐70.3%), followed by gingiva (28.8%; 95% CI = 22.7%‐35.4%) and tongue (27.2%; 95% CI = 21.2%‐33.6%). Regarding geographic location, Middle East presented the highest pooled prevalence (20.8%; 95% CI = 14.8%‐27.6%), followed by America (20.0%, 95% CI = 17.2%‐23%) and Europe (15.6%; 95% CI = 9.2%‐23.5%). Among MiSGT, the MEC overall prevalence was approximately 16.5%. Although most MiSGT were found in the palate, the retromolar area was proportionally more affected by MEC.